Penentuan Metode Transfer Pricing dan Analisis Kesebandingan Sebagai Peniliaian Kewajaran dan Kelaziman Usaha (Arm’s Length Principle) (Studi Kasus Konsultan PT CIA) - Elias, Stefanus; Ramananda, Dimaz (Universitas Pahlawan Tuanku Tambusai, 2025)
Transfer pricing is part of tax and business activities, and its purpose is to ascertain whether the prices used in inter-company transactions with special relationships are based on the principles of reasonableness and business prevalence. As part of taxpayers' compliance with PMK-172 regulations, taxpayers often utilize the services of consultants or third parties. The purpose of this study is to determine PT CIA's basis for conducting comparability analysis and transfer pricing methods. This research is a qualitative case study and uses observation, interviews, and document review to collect data. Based on the results of interviews, comparative analysis, and observations, PT CIA has conducted a comparability analysis and determined the transfer pricing method referring to and in accordance with the OECD Transfer Pricing Guidelines, PER-32/PJ/2011, PER-22/PJ/2013, SE-50/PJ/2013, PMK-213/PMK.03/2016, and PMK-172/2023.